Draft whole-genome sequence of Sphingobium sp. 22B, a polycyclic aromatic hydrocarbon- degrading bacterium from semiarid Patagonia, Argentina - Madueño, Laura (2016)
Sphingobium sp. 22B is a polycyclic aromatic hydrocarbon-degrading strain isolated from Patagonia, Argentina, with capabilities to withstand the environmental factors of that semiarid region. The draft genome shows the presence of genes related with responses to carbon starvation and drying environmental conditions.